In situ Photoluminescence Study of Plasma Effects on Passivation of Crystalline Silicon Coated with Aluminum Oxide. Issue 10 (2nd January 2019) - Sreng, Mengkoing; Silva, François; Roca i Cabarrocas, Pere
Abstract : A degradation of crystalline silicon surface passivation provided by aluminum oxide (Al2 O3 ) is generally observed after plasma processes, e.g., deposition of amorphous silicon nitride. To minimize such detrimental effect, a better understanding of the interaction between plasma species and the Al2 O3 layer is required. Using in situ photoluminescence, the passivation quality of as‐deposited and annealed crystalline silicon wafers coated with Al2 O3 grown by atomic layer deposition is characterized in real time during argon‐hydrogen plasma exposure. The photoluminescence intensity of as‐deposited samples instantly steps up after the plasma ignition, and then it gradually decreases as a function of plasma exposure time. However, only degradation of photoluminescence signal can be found if the samples are annealed prior to the plasma treatment. The interaction between vacuum UV light from plasma and different types of chemical bonds in the Al2 O3 layer is proposed to explain the obtained results. Understanding the mechanisms and root cause leading to different behavior between as‐deposited and annealed samples under plasma exposure is a first step toward redesigning the process flow for better surface passivation. Abstract : Using in situ photoluminescence, the passivation of as‐deposited and annealed Al2 O3 coated c–Si is characterized during argon‐hydrogen plasma exposure. An increase of PL intensity, followed by a gradual degradation is observed on as‐deposited samples, while only degradation is observed on annealed ones. The interaction between UV‐plasma emission and different chemical bonds at Al2 O3 /c–Si interface is proposed to explain the results.